2018
DOI: 10.3390/su10041199
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Commodities and Crude Oil Prices: An Empirical Investigation of Their Relationship

Abstract: Within the last few decades, the extended use of biodiesel and bioethanol has established interlinkages between energy markets and agricultural commodity markets. The present work examines the bivariate relationships of crude oil-corn and crude oil-soybean futures prices with the assistance of the ARDL cointegration approach. Our findings confirm that crude oil prices affect the prices of agricultural products used in the production of biodiesel, as well as of ethanol, validating the interaction of energy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 24 publications
0
38
0
Order By: Relevance
“…Using a VECM model, Chen and Saghaian (2015) showed that the relationship between oil, ethanol, and sugar has become stronger after 2008 in Brazil, where oil price tends to impact the other two variables, while sugar price tends to impact ethanol price. Most of the studies capturing the correlation between oil and agricultural markets interpret such correlations as the transmissions and spillovers from the former to the latter (Koirala et al 2015;Zafeiriou et al 2018;Allen et al 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using a VECM model, Chen and Saghaian (2015) showed that the relationship between oil, ethanol, and sugar has become stronger after 2008 in Brazil, where oil price tends to impact the other two variables, while sugar price tends to impact ethanol price. Most of the studies capturing the correlation between oil and agricultural markets interpret such correlations as the transmissions and spillovers from the former to the latter (Koirala et al 2015;Zafeiriou et al 2018;Allen et al 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, they examine volatility transmission by using the Dynamic Conditional Covariance (DCC)-Generalized Autoregressive Conditional Heteroscedasticity (GARCH) approach and find that both commodities volatility affects each other which is important for diversified portfolio allocation. Zafeiriou et al (2018) examine the relationship between crude oil, corn and soybean futures monthly data over the period of 1987 to 2015 by using autoregressive distributed lag (ARDL) approach. They find that crude oil price affects the prices of ethanol and agricultural products.…”
Section: Vecmmentioning
confidence: 99%
“…Individual types of waste are increasingly used in various industries [27,28]. In the scientific literature, however, there are no reports on their comprehensive use to obtain a valuable products intended for human consumption.…”
Section: Introductionmentioning
confidence: 99%